2022
DOI: 10.1007/s12144-022-02778-9
|View full text |Cite
|
Sign up to set email alerts
|

An explanatory model of the relationships between sport motivation, anxiety and physical and social self-concept in educational sciences students

Abstract: Motivation plays a key role in the physical-sports field, in the control of disruptive states and in the mental image that people have of themselves. In view of the above, the present study reflects the objectives of identifying and establishing the relationship between sport motivation, anxiety, physical self-concept and social self-concept, broken down into (a) developing an explanatory model of sport motivation and its relationship with anxiety and social and physical self-concept and (b) contrasting the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
(30 reference statements)
1
18
0
1
Order By: Relevance
“…Regarding the effect of sports practice on burnout syndrome, it was observed that participants who practiced more than 3 h of physical activity showed lower scores in emotional exhaustion and depersonalization, with this group showing higher scores in personal fulfillment. The results obtained in the present study are supported by numerous studies [ 38 , 39 ], stating that the regular practice of physical exercise brings numerous benefits at a mental level [ 40 , 41 , 42 ], due to the secretion of neurotransmitters such as serotonin and dopamine [ 16 ]. It was also found that lifestyles that are not very active from a physical sports point of view are related to the presence of a negative personal image [ 43 ].…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the effect of sports practice on burnout syndrome, it was observed that participants who practiced more than 3 h of physical activity showed lower scores in emotional exhaustion and depersonalization, with this group showing higher scores in personal fulfillment. The results obtained in the present study are supported by numerous studies [ 38 , 39 ], stating that the regular practice of physical exercise brings numerous benefits at a mental level [ 40 , 41 , 42 ], due to the secretion of neurotransmitters such as serotonin and dopamine [ 16 ]. It was also found that lifestyles that are not very active from a physical sports point of view are related to the presence of a negative personal image [ 43 ].…”
Section: Discussionsupporting
confidence: 86%
“…Attending Serrano-Parra et al [33] this construct can be categorized into low resilience (first quartile), moderate resilience (second and third quartile), and high resilience (fourth quartile). This scale is divided into five dimensions: (a) Factor 1 reflects the notion of personal competence, high standards and tenacity (PECT) composed of Items 10,11,12,16,17,23,24,25; (b) Factor 2 is related to confidence in one's instincts, tolerance to negative effects and strengthening of the stress effects (TTE) composed of Items 6,7,14,15,18,19,20 The original version [32] obtained good results with a Cronbach's alpha of 0.89 and a test-retest reliability of 0.87 in the general population. In the study by Serrano-Parra et al [33], the general reliability was α = 0.906 and obtained different values for each dimension: selfefficacy-tenacity, α = 0.822; tolerance-strengthening, α = 0.677; acceptance and safe relationships, α = 0.677; control and purpose, α = 0.699; spirituality, α = 0.344.…”
Section: Connor-davidson Resilience Scale (Cd-risc)mentioning
confidence: 99%
“…Physical activity is associated with health promotion on the physical, psychosocial, cognitive, and emotional levels [11,12]. Studies showed that physical activity is a priority element in today's society, with special importance in social and health policies [13,14]. Specifically, physical activity has been considered an essential tool that directly affects the quality of life and presents psychosocial benefits in teaching professionals [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although achievement goal theory and the self-determination theory were published decades ago, they are still dominant theories in scientific explanation of a latent construct of motivation in sport [ 39 ]. Modern integrative hierarchical and multidimensional models of motivation in sport are based on these two basic theories [ 40 ].…”
Section: Dynamic Interactive Model Of Sport Motivationmentioning
confidence: 99%